Case report. Postcardiac injury syndrome following radiofrequency ablation for atrial fibrillation and atrial flutter - Y. Suslina; M. Meshkova; A. Doronin (Ukrainian Journal of Cardiovascular Surgery, 2017)
Post-cardiac injury syndrome (PCIS) is a common term that covers such inflammatory pericardial syndromes: post-myocardial infarction pericarditis, post-pericardiotomy syndrome, iatrogenic and non-iatrogenic post-traumatic pericarditis. Rates of this pathology are rather high in a cardiosurgical practice (from 10% to 40%). This article aims at describing a clinical case and focusing on the PCIS as a possible ablation complication.Materials and methods. This article discusses a clinical case of the post-cardiac injury syndrome following the radiofrequency catheter ablation of atrial fibrillation and atrial flutter.Results and discussion. For the treatment of pathology successfully used NSAIDs and colchicine.Conclusions: despite high PCIS rates in a cardiosurgical practice, this abnormality as it follows catheter ablations is rarely reported. Transthoracic echo and monitoring of inflammatory blood markers, in particular CRP, are central to PCIS diagnosis. NSAIDs and colchicine are used to treat the PCIS.